Attractin Gene Deficiency in Rats Leads to Impairments in Both Activity and Spatial Learning and Memory. (1st July 2021) - Li, Xiao-Hui; Xue, Cheng; Liu, Meng-Qi; Zhang, Meng-Yu; Zhou, Yang; Xiao, Xu; Wang, Jia; Xu, Xi-Jia; Shi, Yun; Zhang, Wei-Ning
Highlights: The knocking in ATRN-G505C rats were introduced. Mutations in the Attractin (ATRN) gene lead to motor deficits, and learning and memory impairments. Expression of brain-derived neurotrophic factor (BDNF) was reduced in the ATRN rat hippocampus. Abstract: Attractin (ATRN), an autosomal recessive gene that is widely distributed in the brain, is involved in the execution of a variety of brain functions and associated with certain neuropsychiatric disorders. Here, we introduce a novel rat strain harboring a mutation in ATRN that was generated by knocking in ATRN-G505C via the CRISPR/Cas9 system. We assessed the behavioral performance of these mutant ATRN knock-in rats. The G505C mutation was introduced into exon 9, and a synthetic primer was inserted into introns 8-9 for genotyping. The 505th amino acid, a Gly (G) residue, was mutated to a Cys (C) residue, i.e., GGC was mutated to TGC. Behavioral experiments showed that homozygous ATRN rats spent significantly more time searching for the escape platform in the acquisition trial and significantly less time in the target area in the probe trial in the Morris water maze (MWM) test and traveled a significantly shorter distance in the open field test (OFT) than wild-type rats. In addition, Western blot analysis and immunohistochemistry showed that rats with the mutant ATRN gene exhibited significantly reduced expression of brain-derived neurotrophic factor (BDNF). In summary, our results indicate that mutations in the ATRN gene directly lead to learning and memory impairments and slight motor deficits. These findings provide new clues for the mechanism by which mutant ATRN induces neurodegenerative changes.